Dimension of Human Perfection Based on the Quran - Yusuf, Muhammad; Nahdhiyah, Nahdhiyah; Suardi Wekke, Ismail (Opción, 2019)
The aim of the study is to investigate dimension of human perfection based on the Quran via comparative qualitative research method. As a result, using many different words to designate one object gives an indication of different contents within it. For this reason, a thematic-comprehensive study of the concept of the Quran is needed to describe human being as a whole. In conclusion, every term used by the Quran to explain humanity gives a picture of the human dimension and the whole term used by the Quran which designates human meaning as a separate entity.